Investigation of the electrical properties of metal chalcogenide thin films: A review - Ho, Soon Min (Scholars Research Library, 2016)
In the present study, thin films have been successfully prepared by using various deposition methods. The electrical behaviors of obtained thin films were investigated by using Hall Effect measurement and Van Der Pauw technique as reported by many researchers. The experiment results show that the electrical resistivity reduces with increase in temperature and film thickness as well.